Mapping the Key Actors of Rural Land Conflicts in Bangladesh - Rahman, Md. Zarif; Korobi, Sadia Aktar (Journal of Humanities and Social Sciences (JHASS), 2024)
Conflicts over rural land have plagued Bangladesh since its independence. Rural land issues continue to remain unresolved, and violence related to land is still on the rise. The investigation of those engaged in these disputes and the dynamics of their relationships, however, has received very little attention. The current study maps those involved in land conflicts and their relational interplay in the context of rural Bangladesh. The study utilizes qualitative method of data collection including KII interviews, focus group discussions, and expert interviews. Through purposive sampling, key informant interviews and focus group discussions involved a group of relevant stakeholders in land conflicts in the study areas who provided needed information, ideas, and insights on land issues in the area. The study finds that the power structure of the village affects benefit distribution and the resolution of land disputes. Local political leaders and "Matbors" have an impact on how disputes are resolved. Law enforcement authorities are ineffective at resolving violent conflicts, and corrupt land office staff are also of no help, prolonging such conflicts. The study suggests holding workshops on empathy-building, digitizing land management, and enhancing the court system to lessen disputes amongst stakeholders in rural Bangladesh.